Postoperative Analgesic Effect of Dexamethasone Added To Ropivacaine for Fascia Iliaca Compartment Block Following Femoral Fracture Surgeries - Sharma, Sagun; Baral, Pankaj; Shah, Parasmani; Rayamajhi, Asmita (Journal of Nepalgunj Medical College, 2023)
Introduction: Pain is associated with higher perioperative morbidity in fracture patients. Fascia iliaca compartment block is a simple, inexpensive, and effective method of analgesia for femoral fracture surgeries. Many adjuvants have been used with local anaesthetics to prolong post-operative analgesia. Aims: To assess the effects of dexamethasone as an adjuvant to fascia iliaca compartment block on prolongation of post-operative analgesia in patients undergoing femoral fracture surgeries. Methods: Seventy patients aged, 18-65 years with American Society of Anaesthesiologist-Physical Status I and II, undergoing femoral fracture surgery, were randomly assigned to two groups, n=35 each, who received standard subarachnoid block. Ultrasound guided Fascia iliaca compartment block was given after completion of surgery with 20ml of 0.35% ropivacaine + 2ml normal saline to group one or 20ml of 0.35% ropivacaine + 2ml dexamethasone(4mg/ml) to group 2. Total duration of analgesia and total rescue analgesic requirement in the first post operative day were noted after successful block. Results:The demographic information for the two groups was comparable. The duration of postoperative analgesia was prolonged in patients receiving dexamethasone adjuvant (541 ± 167 vs. 638± 165 mins, p = 0.018; Mean difference -97). Patients receiving dexamethasone adjuvant required significantly less postoperative rescue analgesics for the first 24 hours (tramadol 88 ± 32 vs 65 ± 23 mg, p = 0.001; Mean difference 23). Conclusion: Dexamethasone, added to Fascia Iliaca Compartment Block, as an adjuvant, significantly prolongs the postoperative analgesic effect thereby, reducing the need for rescue analgesic in the first postoperative day.